2001
DOI: 10.1016/s0925-4773(01)00523-8
|View full text |Cite
|
Sign up to set email alerts
|

Notch pathway genes are expressed in mammalian ovarian follicles

Abstract: Folliculogenesis is the process of development of ovarian follicles that ultimately results in the release of fertilizable oocytes at ovulation. This is a complex program that involves the proliferation and differentiation of granulosa cells. Granulosa cells are necessary for follicle growth and support the oocyte during folliculogenesis. Genes that regulate the proliferation and differentiation of granulosa cells are beginning to be elucidated. In this study, the expression patterns of Notch receptor genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 60 publications
2
81
0
Order By: Relevance
“…Thus, in the intestinal mucosa Notch signaling may have a classical 'lateral inhibition' function in the fate choice between the enterocyte lineage and the secretory lineage, and a prodifferentiation 'instructive' role in enterocyte development. Sequential Notch receptor activation has been suggested to occur during spermatogenesis (Mori et al, 2003) and in ovarian follicles (Johnson et al, 2001). There is strong evidence that Notch signaling participates in mammalian brain development, primarily inhibiting neuronal differentiation and allowing/ promoting glial differentiation (Morrison et al, 2000;Grandbarbe et al, 2003).…”
Section: Other Organs and Tissuesmentioning
confidence: 99%
“…Thus, in the intestinal mucosa Notch signaling may have a classical 'lateral inhibition' function in the fate choice between the enterocyte lineage and the secretory lineage, and a prodifferentiation 'instructive' role in enterocyte development. Sequential Notch receptor activation has been suggested to occur during spermatogenesis (Mori et al, 2003) and in ovarian follicles (Johnson et al, 2001). There is strong evidence that Notch signaling participates in mammalian brain development, primarily inhibiting neuronal differentiation and allowing/ promoting glial differentiation (Morrison et al, 2000;Grandbarbe et al, 2003).…”
Section: Other Organs and Tissuesmentioning
confidence: 99%
“…Johnson et al showed differing expression levels of Notch and its ligands for different follicle sizes in an immunohistochemical study; they also emphasized that Notch2 immunopositivity was noted in all the stages of folliculogenesis and that Notch2 immunopositivity was strongly correlated with that of Notch3 [1]. They also reported that mature oocyte development can be disturbed unless Notch2 is absent; this disturbance can be a cause of infertility.…”
Section: Discussionmentioning
confidence: 98%
“…The Notch signaling pathway is initiated by interaction between the extracellular domains of Notch receptors and their ligands on the surface of adjacent cells [16]. Although there are many publications on the importance of the Notch signaling for tissue development [1,[17][18][19][20], only a few studies have been performed on the effects of Notch signaling on oocyte growth. To date, no information is available on human cumulus cells and oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations